2016
DOI: 10.5152/iao.2015.1412
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress and Inflammatory Mediators in Benign Paroxysmal Positional Vertigo

Abstract: OBJECTIVE:Benign paroxysmal positional vertigo (BPPV) is the most common peripheral cause of vertigo. It can be defined as transient vertigo induced by rapid changes in head position associated with a characteristic paroxysmal positional nystagmus. The aim of this study was to search for the possible role of oxidative stress and inflammatory mediators in the pathogenesis of BPPV. MATERIALS and METHODS:Total antioxidant status as well as paraoxonase, tumor necrosis factor alpha, interleukin (IL) 6, and IL-1β le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…Consistent with our findings, Güçlütürk et al [19] confirmed the role of oxidative stress, using native thiol/sulfide (SH/SS) homeostasis as a novel indicator, in the etiology of BPPV. Recent studies have suggested that oxidative stress and inner ear diseases are related.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our findings, Güçlütürk et al [19] confirmed the role of oxidative stress, using native thiol/sulfide (SH/SS) homeostasis as a novel indicator, in the etiology of BPPV. Recent studies have suggested that oxidative stress and inner ear diseases are related.…”
Section: Discussionsupporting
confidence: 91%
“…The occurrence of inflammatory reaction and oxidative stress may play role in the occurrence of vascular vertigo and BPPV [15,17]. Several prior studies have explored the association between serum oxidative stress markers' concentrations and BPPV [19,28]. To the best of our knowledge, it is the first time to measure serum level of SOD in Chinese patients with BPPV and further assess its association with BPPV recurrence events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum IL-6 levels in the CV and PV groups were increased compared with the controls. A previous study investigated the roles of oxidative stress and inflammatory mediators in BPPV and vascular vertigo (50,51). The levels of pro-inflammatory mediators, including IL-6, were higher in the BPPV group and decreased with a repositioning maneuver (50).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the roles of oxidative stress and inflammatory mediators in BPPV and vascular vertigo (50,51). The levels of pro-inflammatory mediators, including IL-6, were higher in the BPPV group and decreased with a repositioning maneuver (50). The IL-6 levels in vascular vertigo were also significantly higher than those of non-vascular vertigo and controls (51).…”
Section: Discussionmentioning
confidence: 99%